Treatment and Outcome of Osteoporotic Thoracolumbar Vertebral Body Fractures With Deformation of Both Endplates With or Without Posterior Wall Involvement (OF 4): Short-Term Results from the Prospective EOFTT Multicenter Study. Issue 1 (April 2023) - Spiegl, Ulrich J. A.; Schenk, Philipp; Schnake, Klaus John; Ullrich, Bernhard W.; Osterhoff, Georg; Scheyerer, Max J.; Schmeiser, Gregor; Bäumlein, Martin; Scherer, Michael A.; Müller, Michael; Sprengel, Kai; Liepold, Katja; et al.
Study Design: Multicenter prospective cohort study Objective: To analyse therapeutical strategies applied to osteoporotic thoracolumbar OF 4 injuries, to assess related complications and clinical outcome. Methods: A multicenter prospective cohort study (EOFTT) including 518 consecutive patients who were treated for an Osteoporotic vertebral compression fracture (OVCF). For the present study, only patients with OF 4 fractures were analysed. Outcome parameters were complications, Visual Analogue Scale, Oswestry Disability Questionnaire, Timed Up & Go test, EQ-5D 5L, and Barthel Index after a minimum follow-up of 6 weeks. Results: A total of 152 (29%) patients presented with OF 4 fractures with a mean age of 76 years (range 41-97). The most common treatment was short-segment posterior stabilization (51%; hybrid stabilization in 36%). Mean follow up was 208 days (±131 days), mean ODI was 30 ± 21. Dorsoventral stabilized patients were younger compared to the other groups ( P < .001) and had significant better TuG compared to hybrid stabilization ( P = .049). The other clinical outcomes did not differ in the therapy strategies (VAS pain: P = 1.000, ODI: P > .602, Barthel: P > .252, EQ-5D 5L index value: P > .610, VAS-EQ-5D 5L: P = 1.000). The inpatient complication rate was 8% after conservative and 16% after surgical treatment. During follow-up period 14% of conservatively treated patients and 3% of surgical treated patients experienced neurological deficits. Conclusions: Conservative therapy of OF 4 injuries seems to be viable option in patients with only moderate symptoms. Hybrid stabilization was the dominant treatment strategy leading to promising clinical short-term results. Stand-alone cement augmentation seems to be a valid alternative in selected cases.